APPLIED PRODUCTIVITY MEASUREMENT WITH OBJECTIVE MATRIX (OMAX) METHOD (Case Study: Service Department in PT. Astra International Tbk Auto 2000 - Kenjeran Branch) - suparto, suparto (UNIPA PRESS, 2019)
Astra International Tbk. Auto 2000 branch Kenjeran is a company department in sales, service and spare parts services. To evaluate the productivity in the service department for this time, it is necessary to measure productivity properly and correctly because productivity measures can be used as material for consideration in carrying out an upcoming productivity planning. This research was conducted in January-December 2013. The productivity method used is the Objective Matrix (OMAX) method. From the results of productivity measurements, it is known that the best productivity occurs in July, which is equal to 768.8, well above the standard value of 300. The worst productivity occurred in February, which amounted to equal 174,8. From the achievement of the score it can be seen that the criteria that do not contribute to the productivity index are criteria 1, namely the comparison between unit handling and the use of working hours because it has the smallest score to equal 47. The strategy for increasing productivity is to evaluate the causes of decreasing productivity in the lowest criteria.